STUDY COMPARING PREEMPTIVE ANALGESIC EFFECTS OF ORAL GABAPENTIN AND CLONIDINE AGAINST PLACEBO IN TOTAL ABDOMINAL HYSTERECTOMY UNDER COMBINED SPINAL EPIDURAL ANAESTHESIA - DR AMMINIKUTTY C M; DR BIJI K P (International Journal of Pharma and Bio Sciences, 2015)
Abdominal hysterectomy usually requires multimodal analgesic regimen for optimal perioperative analgesia. Through this study we aim to assess the significance of preemptive analgesia as well as to compare the efficacy of two analgesics - Clonidine and Gabapentin in abdominal hysterectomy. To compare the postoperative analgesia, sedation and side effects of oral Gabapentin, Clonidine and placebo given as preemptive analgesics in patients undergoing Total Abdominal Hysterectomy under Combined Spinal Epidural Anaesthesia Design. Randomized Controlled study . One hundred and twenty American Society of Anesthesiologists’ Physical Status 1& 2 patients posted for elective abdominal hysterectomy were randomly allocated into three groups- group G received preemptive analgesia with T. Gabapentin 300mg, Group C –T. Clonidine 0.15mg and Group P –Placebo. Hysterectomy was performed under combined spinal epidural. Patients were assessed 24hours postoperatively for pain using numerical rating scale, sedation using Macintyre Sedation Scale and other complications. Pain managed with epidural boluses and breakthrough pain with inj. Diclofenac. Total analgesic consumption in 24hours noted.There is significant difference in pain scores at 12 and 24 hours; P values 0.001 and 0.049 respectively. P value is 0.003 when break through pain is compared among groups; Significant difference noted between G and C (P=0.014). There is significant difference in the number of epidural and total analgesia taken by the three groups with P value < 0.001.No statistically significant difference in sedation scores and side effects. Preemptive analgesia has a definite role in reducing analgesic requirements. 300mg of Gabapentin has better preemptive analgesic effects when compared to 0.15mg of Clonidine.